QoG OECD Dataset - Teorell, Jan; Kumlin, Staffan; Holmberg, Sören; Rothstein, Bo; Sundström, Aksel; Quality of Government Institute, University of Gothenburg (University of Gothenburg, 2020)
The QoG Institute is an independent research institute within the Department of Political Science at the University of Gothenburg. The main objective of our research is to address the theoretical and empirical problem of how political institutions of high quality can be created and maintained.

To achieve said goal, the QoG Institute makes comparative data on QoG and its correlates publicly available. To accomplish this, we have compiled several datasets that draw on a number of freely available data sources, including aggregated individual-level data.

The QoG OECD Datasets focus exclusively on OECD member countries. They have a high data coverage in terms of geography and time.
In the QoG OECD TS dataset, data from 1946 to 2021 is included and the unit of analysis is country-year (e.g., Sweden-1946, Sweden-1947, etc.).

In the QoG OECD Cross-Section dataset, data from and around 2018 is included. Data from 2018 is prioritized, however, if no data are available for a country for 2018, data for 2019 is included. If no data for 2019 exists, data for 2017 is included, and so on up to a maximum of +/- 3 years. In the QoG OECD Time-Series dataset, data from 1946 to 2021 are included and the unit of analysis is country-year (e.g. Sweden-1946, Sweden-1947 and so on).

The QoG OECD Datasets focus exclusively on OECD member countries. They have a high data coverage in terms of geography and time.

In the QoG OECD Cross-Section dataset, data from and around 2018 is included. Data from 2018 is prioritized, however, if no data are available for a country for 2018, data for 2019 is included. If no data for 2019 exists, data for 2017 is included, and so on up to a maximum of +/- 3 years. In the QoG OECD Time-Series dataset, data from 1946 to 2021 are included and the unit of analysis is country-year (e.g. Sweden-1946, Sweden-1947 and so on).

QoG-institutet är ett oberoende forskningsinstitut vid Statsvetenskapliga institutionen vid Göteborgs universitet. Det huvudsakliga syftet med vår forskning är att besvara den teoretiska och empiriska frågan hur politiska institutioner av hög kvalitet kan skapas och upprätthållas.

För att uppnå detta syfte tillgängliggör vi jämförande data om QoG och dess korrelationer till allmänheten. För att åstadkomma detta har vi sammanställt flera datamängder som bygger på ett antal fritt tillgängliga datakällor, inklusive aggregerad data på individnivå.

QoG OECD Dataset fokuserar uteslutande på OECD:s medlemsländer. De har en hög datatäckning vad gäller geografi och tid med variabler relaterade till Quality of Government.

I QoG OECD Cross-Section dataset ingår data från omkring 2018. Data från 2018 är prioriterat, men där inga uppgifter finns tillgängliga från 2018 för ett specifikt så ingår data för 2019. Om inga uppgifter finns tillgängliga för 2019 så ingår data för 2017 och så vidare upp till max +/- 3 år. I QoG OECD Time-Series dataset ingår data från 1946 till 2021 och analysenheten är land-år (t.ex. Sverige-1946, Sverige-1947 och så vidare).
QoG OECD Dataset
Keywords: STATE CONTROL; STATLIG STYRNING; LABOUR AND EMPLOYMENT; ARBETE OCH SYSSELSÄTTNING; GOVERNMENT; REGERING; POLITICAL INSTITUTIONS; POLITISKA INSTITUTIONER; CORRUPTION; KORRUPTION; DATA; DATA; BUREAUCRACY; BYRÅKRATI; CENTRAL GOVERNMENT; CENTRALREGERING; PUBLIC ADMINISTRATION; OFFENTLIG FÖRVALTNING; GOVERNMENT ORGANIZATIONS; STATLIGA ORGANISATIONER; POLITICAL SYSTEMS; POLITISKA SYSTEM; Government, political systems and organisations; Regering, politiska system och organisationer; Social Sciences; Samhällsvetenskap; Political Science; Statsvetenskap